2012
DOI: 10.5402/2012/153412
|View full text |Cite
|
Sign up to set email alerts
|

Constraints to On-Farm Maize (Zea mays L.) Seed Production in Western Kenya: Plant Growth and Yield

Abstract: Studies have shown that that about 85% of maize farmers in Western Kenya plant local varieties with about 80% using own farm-saved seeds. The production system is characterized by late harvesting, heavy striga infestation, use of local varieties, and low-soil fertility. The objective of this study was to test an on-farm seed production system which would help improve yield and quality of farm saved seeds. The trials were set up in a factorial design fitted as random complete block design. There were 3 factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…Next to Fusarium spp., the other Analysis of soil pH was conducted according to Otinga et al (2013). Organic carbon and nitrogen contents were determined following the protocol of Okalebo et al (2002), while extractable soil phosphorus was determined according to Olsen et al (1954) a Kihoro et al 2013 b Atieli et al 2009 c Wambugu et al 2012d Ohaga et al 2007 common taxa in the irrigated ecosystems were Curvularia and Talaromyces (Supplementary Table 1). …”
Section: Rice Endophytic Fungi From Irrigated and Upland Ecosystemsmentioning
confidence: 99%
“…Next to Fusarium spp., the other Analysis of soil pH was conducted according to Otinga et al (2013). Organic carbon and nitrogen contents were determined following the protocol of Okalebo et al (2002), while extractable soil phosphorus was determined according to Olsen et al (1954) a Kihoro et al 2013 b Atieli et al 2009 c Wambugu et al 2012d Ohaga et al 2007 common taxa in the irrigated ecosystems were Curvularia and Talaromyces (Supplementary Table 1). …”
Section: Rice Endophytic Fungi From Irrigated and Upland Ecosystemsmentioning
confidence: 99%
“…These resultant landraces may be low yielding but are able to cope up with many biotic and abiotic stresses due to their heterogeneity and are therefore likely to lead to yield stability. Studies have shown that farmers prefer yield stability to maximum obtainable yields in line with their strategy of risk avoidance (Almekinders and Louwaars 1999 ; Wambugu et al 2012 ). This observation is confirmed by reports that farmers in some parts of West Africa such as the Banfora area in Burkina Faso are abandoning improved rice varieties in favour of the low yielding but highly adaptable Oryza glaberrima varieties (Futakuchi et al 2012 ).…”
Section: Reviewmentioning
confidence: 99%
“…Although maize yield was low than reported elsewhere in SSA, it was within the range (0.6 to 5.0 Mg ha -1 ) reported in western Kenya (Wambugu, Mathenge, Auma, & VanRheenen, 2012). The observed lower yields of maize with increasing soybean population can be attributed to a reduction in maize plant population as in most cases no significant differences were detected between D1 and SM, treatments which had the same maize plant population.…”
Section: Soybean and Maize Grain Yieldmentioning
confidence: 38%